Procedimento numérico e experimental para projeto estrutural de barras de pulverização - Cappellari, Állex Sander (2019)
Sprayers are equipment designed to dissipate liquids into small fragments to atomize and distribute drops of pesticides on cultivars. Sprayer booms are slender structures, which usually resemble triangular lattices, with the largest dimension horizontally and perpendicular to the direction of travel of the machine, fixed in the central region with free ends. The function of the boom is to carry the spray nozzle, positioning it with stability in a certain working range. Thus, the productive capacity of the sprayer is directly related to the width of the bars that determines the reach of the pesticides, which motivates the development of larger bars. The present work aims to determine a structure development procedure for spray booms, with numerical and experimental approach with consideration of dynamic effects and fatigue phenomena, with the purpose of developing high efficiency structures. Initially, input data, objectives and requirements for procedure development are defined, such as the size of the bar to be developed and concepts to be compared. For structural evaluation of the chosen concept, base excitations imposed on the structure and the structural damping ratio were experimentally measured. Transient finite element analyses were performed to determine the dynamic response and to provide the stress history, making it possible to predict the fatigue life of the welded joints of the sprayer boom, using SN curves experimentally determined for each type of analyzed joint.